Challenges of Corrosion, Wear, Erosion, and Abrasion in Hydropower Plants: Materials, Modeling, and Mitigation Strategies - Singh, Harvinder (Engineering Transactions, 2026)
The chemical, food processing, hydropower, thermal power, and oil industries are among the sectors that frequently face the problems of erosion, abrasion, and corrosion. Pipelines, elbows, reducers, separators, tees, and seals are among the hydraulic devices and pipeline components that are impacted by these difficulties. Silt erosion in turbines and related parts is a major issue in hydropower plants, particularly in Indian hydropower plants where rivers contain hard elements like feldspar, quartz, and other minerals. Remarkably, more than half of the quartz in the silt causes problems in turbines, including sediment erosion, leaks, and secondary flow disturbances. Hydropower plants’ total efficiency is ultimately jeopardized by these issues. This paper aims to support scholars and researchers by highlighting the following topics: (i) component failures in impulse and response turbines used in hydropower projects; (ii) different turbine materials and their properties; and (iii) a comparison of several thermal spraying techniques for turbine materials along with numerous numerical models of erosion and abrasion informed by silt characteristics, material properties, and flow phenomena in different hydro-turbines. The study also discusses modeling, pilot plant loops, wear mechanisms, and protective techniques aimed at mitigating wear and safeguarding hydro turbines.